PKM Pelatihan Mengetik Sepuluh Jari bagi Santri Patriot Panji Pelopor (SP3) Pondok Pesantren Nurul Jadid - Gulpi Qorik Oktagalu Pratamasunu; Latifatul Khoer; Meliana Eka Puteri; Zumrotul Maqfiroh; Yunis Hofifah; Siti Umairah; Nidia Fachrum F. Paputungan; Zahrotunnisa Zahrotunnisa (Universitas Nurul Jadid, 2021)
Currently, ten-finger typing skills have become the general standard for prospective employees who will apply for jobs. These skills are not only needed for IT-based jobs but are also needed in other jobs in the office. Unfortunately, until now, many students still do not have these skills. Therefore, ten-finger typing training for students at the Nurul Jadid Islamic Boarding School is very much needed. The method used in the implementation of this activity is a practice-based training method using the Typing Master and Typer Shark Deluxe applications. The result of this activity is that the participants experienced an increase in typing. Those who previously used two fingers at the end of the meeting can use all their fingers to type.